Pembuatan Alat Penetas Telor Otomatis Untuk Peningkatan Penghasilan Peternak Desa Kertamukti Kec. Cibitung Kabupaten Bekasi - Sigit Panca Priyana; Josua Bertuah Turi Sitompul; Johannes Sipayung; Iyen Martupa Naibaho; Alfian Ady Saputra (Cv. Utility Project Solution, 2023)
The need for food in the form of chicken meat in Indonesia in one year is 3.43 million tons in 2021 (based on BPS). This can only be fulfilled if the continuity of supply chain availability runs smoothly from hatchery, rearing to the food industry. In the International Joint Agreement contained in the DEVISION FOR SUSTAINABLE DEVELOPMENT GOALS (DSDG) which is noted in the second point